(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Resolution of the Cabinet of Ministers of the Republic of Uzbekistan dated December 8, 2018 No 997 "On measures to organize international research in the field of education quality assessment in the public education system" organization, establishment of international relations, research and innovation activities of students and youth, most.First of all, to conduct international research on education quality assessment under the State Inspectorate for Education Quality Control under the Cabinet of Ministers of the Republic of Uzbekistan in order to fully support and encourage the creative ideas and creativity of the younger generation. national center was established.